Unveiling Digital Transparency: Internet-Based Financial Reporting Disclosure by Indonesian Local Governments - Fifi Yusmita; Arif Kurniawan (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
Internet Financial Reporting Disclosure (IFRD) represents a critical instrument for enhancing transparency and public accountability in local government, as mandated by the Ministry of Home Affairs Regulation No. 188.52/1797/SJ of 2012 however, its implementation remains uneven across regions. This study examines the effect of Local Own Source Revenue, Local Expenditure, Audit Opinion, and Size of Local Government on IFRD in Indonesia. Employing a quantitative approach with panel data from 2020 to 2023, this study analyzes 126 observations selected through purposive sampling and applies panel data regression using EViews 12, following model selection and classical assumption tests to ensure robustness. The empirical results demonstrate that all independent variables have a positive and significant effect on IFRD, indicating that stronger fiscal capacity, higher expenditure allocation, favorable audit outcomes, and larger institutional scale are associated with greater financial disclosure. These findings are consistent with Signalling Theory, suggesting that well-performing local governments tend to disclose more information to reduce information asymmetry and signal accountability to the public. Furthermore, the results highlight that transparency is shaped by the combined influence of financial performance and institutional characteristics rather than a single determinant. These findings imply that strengthening financial management, improving audit quality, and enhancing institutional capacity are essential to optimize internet-based financial disclosure, reinforce public trust, and support the effective implementation of good governance in local governments.